A novel automated methodology that estimates the United Nations (UN) Sustainable Development Goal (SDG) 14.1.1.: Index of coastal eutrophication using the Copernicus Marine Environment Monitoring Service (CMEMS) - Sarelli, Anastasia; Sykas, Dimitris; Miltiadou, Milto; Bliziotis, Dimitris; Spastra, Yiota; Ieronymaki, Maria (My University, 2018)
The aim of the SDGs is to help human activities be sustainable. The SDG14 "Oceans" targets at the stability and sustainability of marine ecosystems and their resources. Among its ten targets, the 1st refers to the prevention and the significant reduction of marine pollution of all kinds. To quantify the target, the 14.1.1 "Index of Coastal Eutrophication (ICEP) and Floating Plastic Debris Density" is introduced by UNEP. Currently, classified in Tier III, i.e. the methods and data sources for its estimation are not defined, whereas the type of information needed is defined. It is composed from two sub-indicators: Coastal eutrophication, and concentration of floating plastic. According to the Oslo-Paris Convention, "eutrophication means the enrichment of water by nutrients causing an accelerated growth of algae and higher forms of plant life.". The impact of this sub-indicator can be characterized as social (waters dangerous for health) and economic (fish/mussels die resulting to production losses), while it has legislation implications (Marine Strategy Framework Directive). Eutrophic areas are usually detected in coastal waters due to nutrient inputs from anthropogenic coastal and land activities. CMEMS uses EO data and in-situ measurements to model these types of information. In this paper we present a novel automatic methodology to calculate the SDG14.1.1.a in the regions of Iberia-Biscay-Ireland Seas. The methodology exploits CMEMS models of Phosphate-Nitrates-Silica-Chlorophyll and Water-Transparency to calculate a weighted indicator that segments waterbodies into four categories: Non-problem areas, tendency in eutrophication events, possibility of eutrophication events and problem areas. The indicator was calculated with respect to bathymetry and the Exclusive Economic Zones of the countries that are included in the region, while the temporal provision was weekly and monthly, aggregated from daily CMEMS products. Results indicate the distribution of problematic waters near high population density areas and river estuaries and the shallow waters' tendency in eutrophication events.
Keywords: Chlorophyll; Copernicus Marine Environment Monitoring Service (CMEMS); Earth Observation modeling; Index of Coastal Eutrophication; Nutrients; Sustainable Development Goals (SDGs); Water Quality; Zecchi Depth